2017
DOI: 10.1016/j.scitotenv.2017.06.067
|View full text |Cite
|
Sign up to set email alerts
|

An in situ method for the high resolution mapping of 137Cs and estimation of vertical depth penetration in a highly contaminated environment

Abstract: The Chernobyl nuclear power plant meltdown has to date been the single largest release of radioactivity into the environment. As a result, radioactive contamination that poses a significant threat to human health still persists across much of Europe with the highest concentrations associated with Belarus, Ukraine, and western Russia. Of the radionuclides still prevalent with these territories Cs presents one of the most problematic remediation challenges. Principally, this is due to the localised spatial and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In this study, the software package Monte Carlo N-Particle 5 code (MCNP5) was used to obtain spectral responses in order to derive PVR values for appropriate depth distribution (Briesmeister, 1993). To ensure that each depth distribution could be adequately modelled, disk-shaped source descriptions measuring 10 mm thick were simulated down to a depth of 70 g cm -3 (Varley et al, 2017). In this manner the PVR could be defined with higher depth resolution and facilitated improved counting statistics as the maximum particle number in MCNP5 (2Ă—10 -9 ) could be run for each simulation, thereby effectively increasing the source density without repeated random number sampling (Hendriks et al, 2002).…”
Section: Detector Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the software package Monte Carlo N-Particle 5 code (MCNP5) was used to obtain spectral responses in order to derive PVR values for appropriate depth distribution (Briesmeister, 1993). To ensure that each depth distribution could be adequately modelled, disk-shaped source descriptions measuring 10 mm thick were simulated down to a depth of 70 g cm -3 (Varley et al, 2017). In this manner the PVR could be defined with higher depth resolution and facilitated improved counting statistics as the maximum particle number in MCNP5 (2Ă—10 -9 ) could be run for each simulation, thereby effectively increasing the source density without repeated random number sampling (Hendriks et al, 2002).…”
Section: Detector Calibrationmentioning
confidence: 99%
“…Recently, Varley et al, (2017) demonstrated that through the use of the peak-to-valley ratio (PVR) improved inventory estimates could be made for aged Chernobyl deposits in Belarus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can have significant impact on the decommissioning cost because these materials are usually present in large volumes in contaminated sites [2]. Sources of contamination of this porous materials especially soil include fall out from nuclear weapons testing; nuclear accidents e.g., the Chernobyl and Fukushima accidents; and poor disposal of nuclear wastes [3][4][5]. In addition, the presence of these contaminants in the soil constitute a major public hazard due to their long half-life and chemical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional methods of depth estimation such as core sampling and logging are slow and have limited spatial sampling extent because of their intrusive nature. Furthermore, the nonintrusive methods reported in [5,[7][8][9][10][11][12][13][14] are either based on regressional models whose parameters typically have no physical significance or are limited to specific radioactive sources. Also, other nonintrusive methods reported in [15,16] use specialised shielding and collimator arrangements while those that employ machine learning [17][18][19] require significant amount of data to train the algorithms.…”
Section: Introductionmentioning
confidence: 99%